the Faktor-Faktor Yang Mempengaruhi Kinerja Sistem Informasi Akuntansi (Studi Kasus PT. Petrokimia Gresik) - Muhammad Nafi Aziz; Erry Andhaniwati (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This study determined whether user involvement, top management support, and personal technical skills influence the performance of the accounting information systems. The object of research was PT. Petrokimia Gresik, with a population of 55 employees of the accounting and finance department which obtained a research sample using simple random sampling of 48 respondents. This study uses a partial least square (PLS) analysis technique with the help of smartPLS 3.0. The results showed that user involvement and top management support had a significant effect on the performance of the accounting information system, while personal technical skills had no effect on the performance of the accounting information system.